Kinerja BUMDes dalam Pemberdayaan Masyarakat di Desa Mengwi Kecamatan Mengwi Kabupaten Badung - Rahayu, Ni Putu Gita; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2019)
ABSTRACT Mengwi Village Government established a Village-Owned Business Entity (BUMDes) as a driving force to improve village economy and community empowerment based on village potential. Results of this study is the performance of Mengwi BUMDes has not gone well in terms of output, results, business links with achievement and explanatory information during the 4 years of the estblishment BUMDes. The performance of BUMDes in community empowerment also has not been maximally seen from the indicators of enabling, empowering, and protecting. The obstacles in realizing community empowerment through BUMDes are lack of guidance from local government and less competent human resources. Suggestions that can be give for guidance and guidance from the local government, there needs to be a refresher for the management to realize community empowerment through BUMDes in Mengwi Village. Keywords: Performance, BUMDes, Empowerment